Variation in DRD4 gene methylation in wild great tits is associated with behavioural tolerance to human disturbance but not with habitat urbanization - Ágh, Nóra; Bánlaki, Zsófia; Horváth, Olimpia; Árpási, Zalán; Vincze, Ernö; Seress, Gábor; Mihalik, Bendegúz; Kovács, Bálint; Bukor, Boglárka; Pipoly, Ivett; Barna, János; Rónai, Zsolt; et al. (Journal of Avian Biology, 2025)
The increasing presence and activities of people in both urban environments and non-urban areas result in the exposure of many wild animal populations to persistent human disturbance. As a response, individuals in disturbed populations often become tolerant towards humans, which can have significant ecological and societal consequences, for example by affecting ecosystem services and human–wildlife conflicts. Although several mechanisms have been proposed to explain the emergence and spread of disturbance tolerance, their biological bases are rarely investigated in natural populations. In this study, we investigated behavioural tolerance in great tits Parus major along urbanization gradients of two cities representing different levels of human disturbance. Specifically, we studied whether variation in disturbance tolerance is related to epigenetic variation in the DRD4 gene that is often linked to behavioural plasticity. We did not detect differences in DNA methylation at 23 CpG sites between wild great tit populations breeding in differently urbanized areas. However, variation in methylation at some CpG sites was associated with two proxies of tolerance, return latency and the vigilance behaviour of parent birds measured after standardized disturbance. These findings suggest that epigenetic variation may be involved in the processes generating behavioural tolerance to human disturbance. These results have implications for understanding the mechanisms by which animal populations can respond to disturbances in human-dominated environments.